2017
DOI: 10.4314/sokjvs.v15i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pathological changes of natural infectious bursal disease virus infection in the lymphoid organs of Black Harco pullets

Abstract: This study examined the sequential pathological changes in the lymphoid organs (bursa of Fabricius, thymus, spleen and caecal tonsils) of 7-week-old Harco pullet chicks that showed severe clinical disease and lesions during a natural infection with a virulent infectious bursal disease virus. Clinical signs were sleepiness, droopy appearance, greenish-whitish diarrhoea, anorexia and prostration followed by death. Mortality rate was 78% within 3 days of the infection followed by recovery. Gross lesions were mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(58 reference statements)
1
3
0
1
Order By: Relevance
“…This research was similar with other research that enlarged and hemorrhage in the serosa of bursa Fabricius, slight hemorrhage on the plica bursa of Fabricius were showed (Akter et al, 2018b;Bharathi et al, 2021;Chowdhury et al, 1996;Kulsum et al, 2018;. The acute inflammatory swelling or enlargement of the bursa of Fabricius would occur in few days into the outbreak (Igwe et al, 2017). Bursa of Fabricius would be swollen (enlarged) with increased weight, because of congestion, exudation of fluid into the interfollicular tissues, accumulation of fluid in the necrotized lymphoid follicles forming cysts and presence of mucous, caseous or gelatinous exudate on mucosal folds lining the inside of the bursal lumen (Igwe et al, 2017;Wang et al, 2011).…”
Section: E D B Asupporting
confidence: 89%
See 1 more Smart Citation
“…This research was similar with other research that enlarged and hemorrhage in the serosa of bursa Fabricius, slight hemorrhage on the plica bursa of Fabricius were showed (Akter et al, 2018b;Bharathi et al, 2021;Chowdhury et al, 1996;Kulsum et al, 2018;. The acute inflammatory swelling or enlargement of the bursa of Fabricius would occur in few days into the outbreak (Igwe et al, 2017). Bursa of Fabricius would be swollen (enlarged) with increased weight, because of congestion, exudation of fluid into the interfollicular tissues, accumulation of fluid in the necrotized lymphoid follicles forming cysts and presence of mucous, caseous or gelatinous exudate on mucosal folds lining the inside of the bursal lumen (Igwe et al, 2017;Wang et al, 2011).…”
Section: E D B Asupporting
confidence: 89%
“…The acute inflammatory swelling or enlargement of the bursa of Fabricius would occur in few days into the outbreak (Igwe et al, 2017). Bursa of Fabricius would be swollen (enlarged) with increased weight, because of congestion, exudation of fluid into the interfollicular tissues, accumulation of fluid in the necrotized lymphoid follicles forming cysts and presence of mucous, caseous or gelatinous exudate on mucosal folds lining the inside of the bursal lumen (Igwe et al, 2017;Wang et al, 2011).…”
Section: E D B Amentioning
confidence: 99%
“…The lesions were usually characterized by tissue necrosis, hemorrhage and acute in ammation. The acute in ammatory swelling or enlargement of the BF would occur in few days into the outbreak (Igwe et al, 2017) and was observed in majority (90.9%) of the outbreaks. The BF would be swollen (enlarged) with increased weight, because of congestion, exudation of uid into the interfollicular tissues, accumulation of uid in the necrotized lymphoid follicles forming cysts and presence of mucous, caseous or gelatinous exudate on mucosal folds lining the inside of the bursal lumen (Wang et al, 2011;Igwe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The acute in ammatory swelling or enlargement of the BF would occur in few days into the outbreak (Igwe et al, 2017) and was observed in majority (90.9%) of the outbreaks. The BF would be swollen (enlarged) with increased weight, because of congestion, exudation of uid into the interfollicular tissues, accumulation of uid in the necrotized lymphoid follicles forming cysts and presence of mucous, caseous or gelatinous exudate on mucosal folds lining the inside of the bursal lumen (Wang et al, 2011;Igwe et al, 2017). A few of the outbreaks that were not associated with enlarged BF at postmortem might have been presented at the later stage of outbreak when the in ammation had receded and BF atrophy was setting in due to lymphocytic depletion from necrosis and apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Тим не менш масові вакцинації призвели до деяких негативних наслідки. Так вищезгадані вакцинні штами, розмножуючись у тканинах бурси призводили до значного виснаження фолікулів, по аналогії з високовірулентними вірусами [3]. Вплив українських ізолятів вірусу на бурсу Фабріціуса до сьогодні лишається невстановленим.…”
Section: актуальність (Introduction)unclassified